Structural determinants of cold adaptation and stability in a psychrophilic alpha-amylase - D'Amico, Salvino; Gerday, Charles; Feller, Georges (Slovak Academic Press Ltd, 2002)
peer reviewed The heat-labile alpha-amylase from an Antarctic bacterium is the largest known protein that unfolds reversibly according to a two-state transition, as shown by differential scanning calorimetry. Mutants of this enzyme were produced, carrying intended additional weak interactions of a type found in thermostable alpha-amylases. It is shown that single amino acid side chain substitutions can significantly modify the melting point T-m, the calorimetric enthalpy DeltaH(cal), the cooperativity and reversibility of unfolding, the thermal inactivation rate constant, and the kinetic parameters k(cat) and K-m. Although all mutations were located far from the active site, their overall trend is to decrease both k(cat) and K-m, probably by making the molecule more rigid, but this protects mutants against thermal inactivation.